Drama-Based Pedagogy: Ways of Engaging in Mathematics Learning - Lamihhane, Basanta Raj; Dahal, Niroj; Pant, Binod Prasad (Mathematics Education Forum Chitwan, 2023)
Mathematics education program always falls under public criticism because of being unable to produce desirable outcomes. From the beginning of formal mathematics education programs in Nepal, mathematics teaching-learning activities have been dominated by the informing and pouring pedagogy for preparing final examinations. Mathematics curricula, contents and pedagogical activities have not bridged the gap between official (formal) mathematics and the learners' lifeworld practices that support creating the mathematical 'Othering'. Likewise, mathematics education programs become unclaimed entity at the crossroads in which no one is willing to take sole responsibility and ownership of the programs but orienting to blame others. Such a blaming culture restrains engaged teaching-learning activities. Against this backdrop, this argumentative paper argues for incorporating the DBP in the mathematics classroom to create an engaged teaching-learning environment. We have metaphorically captured the five significant theoretical features of DBP as/for contextual learning, academic enhancement, reflective practice, agentic development and social wellbeing. Finally, we have briefly described the implications of DBP in mathematics classrooms.